Lyrical autobiography in Perseverancia. Poesía inédita 2018-2021 by Rafael Ballesteros (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2025)
Rafael Ballesteros’ poetry breaks his traditional secrecy and starts recreating topics and meanings that have always been present in his works through lyrical autobiography and minimal quotidian anecdotes use. Those topics are critical and social poetry, love and desire as the world’s engines, friendship’s refuge, the confrontation between the unavoidable death and the yearning of immortality, or the metapoetics’ reflexion.